Cytotoxicity of denture base and hard chairside reline materials: a systematic review - Lima Chaves, Carolina de Andrade; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; de Souza, Raphael Freitas; Giampaolo, Eunice Teresinha (Mosby-elsevier, 2012)
Statement of problem. Adverse reactions to the materials used for the fabrication and reline of removable denture bases have been observed.Purpose. The purpose of this study was to systematically review the published literature on the cytotoxicity of denture base and hard reline materials.Material and methods. MEDLINE via PubMed, Google Scholar, and Scopus databases for the period January 1979 to December 2009 were searched with the following key words: (biocompatibility OR cytotoxic* OR allergy OR burning mouth OR cell culture techniques) and (acrylic resins OR denture OR monomer OR relin* OR denture liners). The inclusion criteria included in vitro studies using either animal or human cells, in which the cytotoxicity of the denture base and hard chairside reline resins was tested. Studies of resilient lining materials and those that evaluated other parameters such as genotoxicity and mutagenicity were excluded. Articles published in the English language and in peer-reviewed journals focusing on the cytotoxicity of these materials were reviewed.Results. A total of 1443 articles were identified through the search. From these, 20 studies were judged to meet the selection criteria and were included in the review. In the majority of the studies, continuous cell lines were exposed to eluates of specimens made from the materials, and mitochondrial activity was used to estimate cell viability. The tested acrylic resins were grouped according to 5 major categories: (1) heat-polymerized; (2) microwave-polymerized; (3) autopolymerizing; (4) light-polymerized; and (5) hard chairside reliners.Conclusions. This review provided some evidence that the heat-polymerized resins showed lower cytotoxic effects than autopolymerizing denture base acrylic resins and light or dual polymerized reline resins. However, because of the large number of variables in the reviewed literature, a definitive conclusion could not be drawn. (J Prosthet Dent 2012;107:114-127)